TRANSFORMASI RELASI GENDER (NUR EL-ISLAM : Jurnal Pendidikan dan Sosial Keagamaan, 2014)
Transformation of gender relation provides a construction of a gender sensitiveparadigm. Traditionally in the social and symbolic position women belonged to the privaterecesses of society in family relationships controlled and defned men, in silence. Incontrast to the traditional “man focused perspective feminist analyses evaluates not onlyoutcome but the fundamental concept values and assumption embedded in traditionaltheories which are controlled by men and reﬂect their concerns “gender sensitive feminismseeks to correct the imbalance and unfairness in gender relation system resulting fromthe implementation of perspective excluding attention to the circumstances of women’sgendered lives. Women struggle to transform their position to be equal to men’s positionthere has been many things: there has been a strategy for improving the distribution ofsocial goods between women and men, there has been a goal in its own right, there hasbeen a method of defending women against the worst oppression of women, there hasbeen a way to construct the public (in patriarchal terms) for women, and it terms thatwomen can tolerate.Key word: Transformasi, Relasi, Gender.